UJI TOKSISITAS AIR LIMBAH PENYAMAKAN KULIT MENGGUNAKAN METODE PENGHAMBATAN PERTUMBUHAN LEMNA SP. - Budhi Priyanto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Various organisms, including Lemna sp., have been employed in thetoxicity test of waste, soil, and water. In this experiment Lemna sp. wereexposed to waste water collected from tanneries in Garut, West Java.The experiment system includes liquid medium (macro and micro salts ofMurashige and Skoog), to which a series of concentrations of the pre-filter-sterilized tannery waste water were added aseptically. Aseptic grownLemna sp. were placed on the medium in a density of 10 fronds permedium container. The system was then incubated for 7 days undercontinuous daylight fluorescent lamps and the number of fronds, freshweight and chlorophyll content of the plants were determined. The resultsshow that EC50 of the tannery waste water is 0.66% of waste water. TheLOEC value is 0.1% and the NOEC value could not be determined butshould below 0.1%. This experiment suggests that tannery waste water isdangerous to aquatic plants if it was discharged to public water bodywithout appropriate pre-treatment.